Gestation Length and Overall Performance in the Subsequent Lactation of Dairy Cows Conceiving to Holstein, Jersey, or Angus Semen: An Observational Study - A. L. Scanavez; L. G. Mendonça (Kansas Agricultural Experiment Station Research Reports, 2018)
Breeding strategies adopted by commercial dairy herds have evolved in recent years by incorporating the use of several breeds, including beef sires. Results of such strategies on offspring performance have been studied but reports on the effects on dam’s overall performance after calving are still lacking. The goal of this observational study was to investigate the associations between sire breed of previous conception, gestation length, and postpartum performance of dairy cows. Records from Holstein and crossbred cows from a Kansas commercial herd were extracted. Data pertaining to cows that conceived from Holstein, Jersey, or Angus sires and initiated second lactation or greater from June 2017 to May 2018 were used in this study. Gestation length was shorter for cows that conceived from Holstein (274.9 ± 0.6 days) compared with Angus sires (276.5 ± 0.6 days). Cows that conceived from Jersey sires had the longest gestation length (278.0 ± 0.4 days). For Holstein cows, milk yield in the first 60 days after calving was influenced by sire breed used on the previous lactation. Holstein cows that became pregnant with Holstein sires had the lowest milk yield compared with other permutations of dam and conceptus breeds. Interestingly, sire breed of previous conception did not influence milk yield in the subsequent lactation of crossbred cows. Cows that became pregnant with Angus sires had greatest incidence of postpartum disorders compared with cows conceiving from Jersey or Holstein sires (28.0, 11.5, and 9.4%, respectively). Nonetheless, sire breed of previous conception did not affect probability of culling in the first 60 days after calving. This study presents evidence that breed of conceptus influences gestation length and milk yield of the dam in the subsequent lactation.
Keywords: sire breed; beef semen; gestation length; milk yield